Metamodelling of stiffness matrices for 2D welded asymmetric steel joints. (November 2019) - Loureiro, Alfonso; Lopez, Manuel; Reinosa, J. Manuel; Gutierrez, Ruth; Bayo, Eduardo
Abstract: Beam-column steel joints usually have a semi-rigid behaviour, and this must be taken into account when carrying out a global analysis of the structure. Rotational springs at each side of the joint are commonly used to simulate this behaviour by means of the component method, but asymmetric welded beam-column steel joints are not included in the formulations of Eurocode 3. This research work proposes a new methodology to obtain the stiffness of welded asymmetrical beam-column steel joints, by means of a cruciform element of 4 nodes and 12 DOF, whose stiffness matrix is directly obtained by means of the meta-modelling of its elements using Kriging's method. The authors have carried out a wide study of 754 different asymmetric welded beam-column steel joints, whose finite element models have been analysed, and then the static condensation method has been used to obtain the equivalent condensed stiffness matrix (Kcond) of the cruciform element for the joints belonging to the training set. These matrices have been used to build the Kriging's model, and the rest of joints have been used for testing the method, which yields very good results. The use of meta-modelling methods to obtain the stiffness matrix of the joint is not only easier in its application than the component method, but it also leads to a formulation that is more accurate, and also takes into account the interactions between the different parts of the joint. Highlights: 754 different 2D asymmetric steel joints have been analysed by means of finite element models. Condensed stiffness matrices have been obtained and introduced into a global analysis, with good results compared to FEM. The condensed matrices include the interactions between the different degrees of freedom of the joints. The components of the condensed stiffness matrices have been directly meta-modelled by means of the Kriging's method. The direct meta-modelling of the condensed stiffness matrices leads to very good results without the necessity of a previous FEM of the joint.